2018
DOI: 10.5123/s1679-49742018000100002
|View full text |Cite
|
Sign up to set email alerts
|

Microcefalia no Piauí, Brasil: estudo descritivo durante a epidemia do vírus Zika, 2015-2016

Abstract: there was an outbreak of microcephaly in Piauí, possibly related to infection during pregnancy Zika virus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
18

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 18 publications
0
7
0
18
Order By: Relevance
“…The research site counts with the State Microcephaly Reference Center organized to treat newborns with suspected microcephaly who are offered consultations and evaluation with pediatricians, neuropediatricians, neurosurgeons, neonatologists, ophthalmologists, physiotherapists and obstetricians. As well as complementary exams, such as auditory and eye fundus screening (RIBEIRO et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The research site counts with the State Microcephaly Reference Center organized to treat newborns with suspected microcephaly who are offered consultations and evaluation with pediatricians, neuropediatricians, neurosurgeons, neonatologists, ophthalmologists, physiotherapists and obstetricians. As well as complementary exams, such as auditory and eye fundus screening (RIBEIRO et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
“…A study developed by Silva (2015) revealed that, generally, feelings experienced by mothers when they first see their child 'can vary from positive feelings and lived with great intensity, to negative feelings such as disappointment and denial.…”
Section: Class 1: Feelings Before the Diagnosis Of Microcephalymentioning
confidence: 99%
“…A microcefalia é uma malformação congênita neurológica, na condição em que o encéfalo não se desenvolve adequadamente e o perímetro cefálico (PC) aferido no recém-nascido mostra-se inferior ao esperado para a idade gestacional e para o sexo correspondente, acompanhando muitas vezes alterações no sistema nervoso central (RIBEIRO et al, 2018).…”
Section: Conclusãounclassified
“…A repercussão gerada pela notificação dos casos de microcefalia ocasionou uma maior mobilização dos serviços do Instituto Materno-Infantil de Pernambuco (IMIP), reorganização dos processos de trabalho e desenvolvimento de pesquisas. Ribeiro et al (2018) realizaram um estudo no Piauí que objetivou descrever a ocorrência e as características dos casos de microcefalia no estado durante epidemia do Zika vírus em 2015-2016. A pesquisa foi realizada com dados dos nascidos vivos no período de um ano por meio do SINASC (Sistema de Informações de Nascidos Vivos), do Registro de Eventos em Saúde Pública (RESP) e de busca ativa em prontuários, na qual foi constatado que houve surto de microcefalia no Piauí, possivelmente relacionado à infecção gestacional pelo Zika vírus.…”
Section: Recém-nascidos Versus Microcefaliaunclassified